Perilaku asusila pada anak dan upaya diversi oleh kepolisian kajian sosio-legal - Teguh Suratman; Wika Yudha Shanty (Jurnal Cakrawala Hukum, 2022)
The existence and efforts to protect children are currently regulated in the provisions of laws and regulations, however, there are many deviations that befall children, for example, parents are wrong in providing care, acts of violence against children both physically and psychologically, are involved in criminal acts of decency, sexual deviation, and so on. The negative influence on children is very large, therefore it requires vigilance, accuracy, seriousness, and handled properly and correctly. It is said so because children are the next generation of the nation whose existence will determine the survival and future of the nation. This study is an empirical legal study with a socio-legal research approach, by taking secondary data from the Police which is compared with the provisions of the relevant legislation governing children. Then the data obtained were analyzed descriptively qualitatively, using logic and inductive and deductive reasoning according to the need to solve and analyze the related data. The results of this study provide an academic and practical contribution to the handling of children's problems in Indonesia. Academically provide scientific contributions to child reviewers and researchers in the future. Meanwhile, practically, in dealing with children's cases using a diversion model that is characteristic of today, one of which is the authority of the Police.How to cite item: Suratman, T Shanty, WY (2022). Perilaku asusila pada anak dan upaya diversi oleh kepolisian kajian sosio-legal. Jurnal Cakrawala Hukum, 13(1). doi:10.26905/idjch.v13i1.7441.